Case report of familial sudden cardiac death caused by a DSG2 p.F531C mutation as genetic background when carrying with heterozygous KCNE5 p.D92E/E93X mutation - Yubi Lin; Jiana Huang; Siqi He; Ruiling Feng; ZhiAn Zhong; Yang Liu; Weitao Ye; Xin Li; Hongtao Liao; Hongwen Fei; Fang Rao; Zhixin Shan; et al. (BMC, 2018)
Abstract Background Sudden cardiac death (SCD) induced by malignant ventricular tachycardia (MVT) among young adults with right ventricular cardiomyopathy/dysplasia (ARVC/D) is a devastating event. Parts of ARVC/D patients have a mutation in genes encoding components of cardiac desmosomes, such as desmoglein-2 (DSG2), plakophilin-2 and desmoplakin. Case presentation Here we report a potentially pathogenic mutation in the DSG2 gene, which was identified in a family with ARVC/D using Whole Exome Sequencing (WES) and Sanger Sequencing. In all, Patient III:1 with ARVC/D carried the compound heterozygous mutations of DSG2 p.F531C and KCNE5 p.D92E/E93X, which were both inherited from her mother (II:2), who died of SCD. Carriers of DSG2p.F531C showed various phenotypes, such as ARVC/D, SCD, MVT and dilated cardiomyopathy. For III:1, there were significant low-voltage regions in the inferior-apical, inferior-lateral wall of the right ventricular epicardium and outflow tracts of the right ventricle. Under the guidance of a three-dimensional mapping system, MVT was successfully ablated with an epicardial-endocardial approach targeting for late, double or fragmental potentials after implantable cardioverter-defibrillator (ICD) electrical storms. No VT recurrence was observed during the one year of follow-up. Conclusions When coexisting with heterozygous KCNE5 p.D92E/E93X, heterozygous DSG2 p.F531C as a genetic background was found to predispose to ARVC/D, SCD and MVT, which were successfully ablated using an epicardial-endocardial approach.